Effect of emotional stimulus on response inhibition in people with mild cognitive impairment: an event-related potential study - Wang, Jing; Li, Cheng; Yu, Xiaohong; Zhao, Yue; Shan, Enfang; Xing, Ying; Li, Xianwen (Frontiers in Neuroscience, 2024)
Background: A few studies are emerging to explore the issue of how aging promotes emotional response inhibition. However, there is a lack of empirical study concerning the impact of pathological cognitive impairment on emotional response inhibition. The present study investigated the effect of emotion on response inhibition in people with mild cognitive impairment, the stage of cognitive impairment before dementia. Methods: We used two emotional stop-signal tasks to explore whether the dual competition framework considering limited cognitive resources could explain the relationship between emotion and response inhibition in mild cognitive impairment. Results: The results showed that negative emotions prolonged N2 latency. The Go trial accuracy was reduced in the high-arousal negative conditions and the stop-signal reaction time was prolonged under high-arousal conditions. This study also verified impaired response inhibition in mild cognitive impairment and found that negative emotions prolonged P3 latency in mild cognitive impairment. Conclusions: Emotional information interferes with response inhibition in mild cognitive impairment populations, possibly because emotional information captures more attentional resources, thus interfering with response inhibition that relies on common-pool resources.